Maternal IgA2 Recognizes Similar Fractions of Colostrum and Fecal Neonatal Microbiota - Sánchez-Salguero, Erick; Corona-Cervantes, Karina; Guzmán-Aquino, Hector Armando; de la Borbolla-Cruz, María Fernanda; Contreras-Vargas, Víctor; Piña-Escobedo, Alberto; García-Mena, Jaime; Santos-Argumedo, Leopoldo (Frontiers in Immunology, 2021)
Microbiota acquired during labor and through the first days of life contributes to the newborn's immune maturation and development. Mother provides probiotics and prebiotics factors through colostrum and maternal milk to shape the first neonatal microbiota. Previous works have reported that immunoglobulin A (IgA) secreted in colostrum is coating a fraction of maternal microbiota. Thus, to better characterize this IgA-microbiota association, we used flow cytometry coupled with 16S rRNA gene sequencing (IgA-Seq) in human colostrum and neonatal feces. We identified IgA bound bacteria (IgA+) and characterized their diversity and composition shared in colostrum fractions and neonatal fecal bacteria. We found that IgA2 is mainly associated with Bifidobacterium, Pseudomonas, Lactobacillus, and Paracoccus, among other genera shared in colostrum and neonatal fecal samples. We found that metabolic pathways related to epithelial adhesion and carbohydrate consumption are enriched within the IgA2+ fecal microbiota. The association of IgA2 with specific bacteria could be explained because these antibodies recognize common antigens expressed on the surface of these bacterial genera. Our data suggest a preferential targeting of commensal bacteria by IgA2, revealing a possible function of maternal IgA2 in the shaping of the fecal microbial composition in the neonate during the first days of life.